DEVELOPING ARTISTIC INTEREST AND ABILITIES THROUGH ORNAMENTATION ART IN SCHOOL EDUCATION - Karimova Shamsiyabonu Toxir qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article examines how ornamentation art can be used to develop students’ interest in visual arts and enhance their artistic abilities. The study emphasizes the role of hands-on exercises, creative projects, and guided exploration in fostering aesthetic perception, technical skills, and imaginative thinking. The article highlights how systematic engagement with ornamentation motifs cultivates motivation, appreciation for art, and the ability to express personal ideas creatively. Pedagogical strategies for integrating ornamentation art into school curricula are discussed, with a focus on interactive, project-based, and differentiated learning approaches